Effect of Infill Pattern, Infill Density, and Infill Angle on the Printing Time and Filament Length of 3D Printing - Suteja, Jaya (Jurnal Rekayasa Mesin, 2021)
To optimize the 3D printing process, the influence of its parameters on the performance of the printing process needs to be investigated. This research investigates the effect of infill pattern, infill density, and infill angle on the printing time and the filament material length. First, this research collected the printing time and the filament length data for each combination of infill pattern, infill density, and infill angle. The data collection was conducted by implementing Repetier-Host v.2.1.6 software as a data acquisition tool. Then, the General Linear Model was applied to analyze the effect of infill pattern, infill density, and infill angle on the printing time and filament length. Based on the analysis, higher infill density increases the printing time for each infill pattern and each infill angle. Also, higher infill density increases the filament length for each infill pattern and each infill angle. The implementation of the Gyroid type of infill pattern reduces the required printing time for each density. Meanwhile, the implementation of the 3D honeycomb type of infill pattern increases the filament length for each infill angle. The use of the 45Â° infill angle increases the filament length and printing time. To reduce the filament length and printing time, the 90Â° infill angle should be implemented.